2009
DOI: 10.1089/jwh.2008.1149
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Polycystic Ovary Syndrome on Selected Indicators of In Vitro Fertilization and Intracytoplasmic Sperm Injection Treatment Success

Abstract: Although IVF/ICSI yields more oocytes in the context of PCOS, IVF/ICSI outcomes do not differ significantly by PCOS status. Prospective cohort studies are needed to examine short-term and long-term health effects of PCOS in the context of IVF/ICSI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(18 citation statements)
references
References 33 publications
1
17
0
Order By: Relevance
“…Of a total of 4292 studies identified through the search, 77 studies met the inclusion criteria for the systematic review. For the metaanalysis, 14 studies were excluded (Table S4) on the basis of reporting outcomes in multiple number of pregnancies per woman [16][17][18][19][20][21] and overlapping data, [22][23][24][25][26][27][28][29] resulting in 63 included studies ( Figure 1).…”
Section: Search Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Of a total of 4292 studies identified through the search, 77 studies met the inclusion criteria for the systematic review. For the metaanalysis, 14 studies were excluded (Table S4) on the basis of reporting outcomes in multiple number of pregnancies per woman [16][17][18][19][20][21] and overlapping data, [22][23][24][25][26][27][28][29] resulting in 63 included studies ( Figure 1).…”
Section: Search Resultsmentioning
confidence: 99%
“…Outcomes of interest were reported in a total of n = 224 136 pregnant women comprising 39 retrospective 23,31,[33][34][35][36][37][38][39][40][42][43][44][47][48][49]51,53,54,56,57,59,61,62,65,67,69,70,73,74,78,79,81,84,85,87,[89][90][91] (n = 157 899) and 24 prospective 30,32,41,45,46,50,52,55,58,60,63,64,66,…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies regarding the impact of PCOS or PCOM on oocyte competence are conflicting [28][29][30][31][32][33]. Many factors could have been responsible on this contradiction such as ovulation induction program, patient age and ethnicity [34], and BMI.…”
Section: Discussionmentioning
confidence: 99%